Identification of Potential Biomarkers for Psoriasis by DNA Methylation and Gene Expression Datasets - Liu, Yong; Cui, Shengnan; Sun, Jiayi; Yan, Xiaoning; Han, Dongran (Frontiers in Genetics, 2021)
DNA methylation plays an important role in the pathogenesis of psoriasis through regulating mRNA expressions. This study aimed to identify hub genes regulated by DNA methylation as biomarkers of psoriasis. Psoriatic skin tissues gene expression and methylation datasets were downloaded from Gene expression Omnibus (GEO) database. Subsequently, multiple computational approaches including immune infiltration analysis, enrichment analysis, protein-protein interaction (PPI) network establishment and machine learning algorithm analysis (lasso, random forest, SVM-RFE) were performed to analyze the regulatory networks, to recognize hub genes, and to clarify the pathogenesis of psoriasis. Finally, the hypermethylated genes were used to immune cell infiltration analysis, which revealed that psoriasis skin tissues were mainly composed of dendritic cells activated, mast cells resting and T cells follicular helper etc. Differentially expressed-methylated genes (DEMGs) were identified and partitioned into 4 subgroups and the 97 significantly hyper-methylated and downregulated (hyper-down) genes accounted for the highest proportion (47%). Hyper-down genes were mainly enriched in glucose homeostasis, AMPK signaling pathway, lipid storage disease, partial lipodystrophy and insulin resistance. Besides, insulin receptor substrate 1 (IRS1) was identified as a potential target. These findings provided new ideas for future studies of psoriasis on the occurrence and the molecular mechanisms.